Do demographic and beef eating preferences impact on South African consumers' willingness to pay (WTP) for graded beef?. (April 2019) - Strydom, Phillip; Burrow, Heather; Polkinghorne, Rod; Thompson, John
Abstract: A total of 720 South African consumers sourced from rural and urban backgrounds scored willingness to pay (WTP) for different eating quality grades of beef. The consumers had previously participated in taste panels which scored eating quality of grilled and slow cook samples before grading them as either 2 (unsatisfactory), 3 (good every day), 4 (better than everyday), or 5 (premium) star quality. Consumers provided details on demographic and meat preference traits. Eating quality grade had the largest effect on WTP ( P  < .001). Whether consumers were sourced from urban or rural backgrounds, or had tasted beef prepared using grill or slow cook methods had little effect on WTP ( P  > .05). Similarly, demographic and meat preference traits had little effect of WTP ( P  > .05), with the exception that at the higher meat quality grades older consumers had a lower WTP than younger age groups ( P  < .05), as did households with >8 adult consumers ( P  < .05).